Fast Sensing of Temperature and Strain along Optical Fiber based on Brillouin Scattering - GUAN Guo-fei; SONG Qing-wu; CHEN Zhi-ming; ZHONG Wei-feng; LI Jun (Guangtongxin yanjiu, 2022)
To improve the extraction accuracy, the Savitzky-Golay filter is used to filter the noisy Brillouin spectra. Based on the obtained relatively accurate Brillouin frequency shift, the symmetric part of the Brillouin spectrum is selected according to the raw Brillouin spectrum. Based on the selected spectrum, the Brillouin frequency shift is extracted by the parabolic fitting. Since the proposed method can obtain the Brillouin spectrum with a high degree of symmetry and more calculation time, the improved parabolic fitting method can significantly improve the accuracy of the extracted Brillouin frequency shift in real-time demonstration. This paper considers the original parabolic fitting method, the fitting method based on the pseudo-Voigt model and the improved parabolic fitting method to calculate the Brillouin frequency shift along the optical fiber. The results show that the calculation time of the modified parabola fitting method is longer than that of the original parabola fitting method, but only 1/37~1/28 of that of the fitting method based on the pseudo-Voigt model. The accuracy of the Brillouin frequency shift extracted by the former is similar to that of the latter. The proposed method is effective to realize fast sensing of temperature and strain along the optical fiber.